Therapeutic potential of natural compounds in targeting cancer stem cells: a promising approach for cancer treatment - Ishita Debnath; Moumita Kundu (Discover Oncology)
Abstract Cancer stem cells (CSCs) are a specific subset of cancer cells that possess the ability to self-renew, resist therapies, and promote metastasis, making them a crucial target in cancer treatment. This study investigates the therapeutic potential of natural compounds in targeting CSCs, particularly their ability to inhibit key signaling pathways, induce apoptosis, and alter the tumor microenvironment. This article reviews the molecular mechanisms that maintain CSCs and contribute to their resistance, focusing on the roles of the WNT/β-catenin, Hedgehog, Notch, and PI3K/ATK/mTOR pathways. Several natural compounds, including curcumin, resveratrol, epigallocatechin gallate, and sulforaphane, were assessed for their effectiveness in targeting CSCs. The finding revealed that these natural compounds can inhibit CSC proliferation, enhance sensitivity to chemotherapy, and suppress the tumor-supportive microenvironment. Notably, compounds such as berberine and piperine were found to reverse drug resistance by downregulating efflux transporters, while quercetin and salinomycin selectively induced apoptosis in CSCs. Overall, natural compounds show promising potential for targeting CSCs in therapy. However, challenges related to bioavailability and metabolic stability must be addressed through advanced drug delivery systems and combination therapy.